Code Choice and Meaning of Ganesa Statue in School Area (A Case Study of Linguistics Landscapes) - Ayu Sulasmini, Ni Made; Benu, Naniana M; Mulyawan, I Wayan (e-Journal of Linguistics; Vol 19 No 1 (2025): ejl-JanuaryDO - 10.24843/e-jl.2025.v19.i01.p15, 2025)
This article aimed at investigating the presence of Ganesa statue in the school premises, in terms of the code choice and symbolic meaning. The code choice within  this article  focuses on the language preferences  that it used to communicate the meaning, meanwhile  meaning refers to the physical, material and its symbolic aspects. This is a qualitative research. The data was obtained from  field and library research that further confirmed by an interview with the school authority and priest. It is found that  the signage on the statue is written in Balinese Language by using Balinese script and Latin. Ganesa within this school context, indicates the existence of masculine power of knowledge, displaying aesthetic, and keeping the unworthy away, the statues are also symbolizing the existence of Ganesa as a medium for prayin.